Barriers and facilitators to community participation for preschool age children born very preterm: a prospective cohort study. (9th January 2021) - Cameron, Kate L; FitzGerald, Tara L; Albesher, Reem A; McGinley, Jennifer L; Allison, Kim; Lee, Katherine J; Cheong, Jeanie L Y; Spittle, Alicia J
Abstract : Aim: We compared preschool age children born very preterm with term‐born controls to: (1) understand the association between very preterm birth and community participation, (2) determine if motor impairment or social risk affect participation differently between groups, and (3) understand environmental barriers and supports to participation for parents. Method: Forty‐eight children born very preterm (<30wks' gestation; 22 males, 26 females) and 96 controls (47 males, 49 females) were assessed at 4 to 5 years' corrected age for community participation using the Young Children's Participation and Environment Measure. Motor skills were assessed using the Movement Assessment Battery for Children, Second Edition and the Little Developmental Coordination Disorder Questionnaire. Results: Children born very preterm participated less frequently than term‐born children (difference in means=–0.28, 95% confidence interval [CI] –0.54 to –0.03, p =0.029). Social risk was associated with lower frequency (interaction p <0.001) and involvement (interaction p =0.05) in community activities for children in the very preterm group only. Parents of children born very preterm perceived more barriers (odds ratio=4.32, 95% CI 1.46–12.77, p =0.008) and environmental factors to be less supportive of participation than parents of controls (difference in medians=–6.21, 95% CI –11.42 to –1.00, p =0.02). Interpretation: Children born very preterm may benefit from ongoing support to promote participation, especially in families of higher social risk. What this paper adds: Children born preterm attend community activities less often than term‐born children. When attending community activities, involvement was similar between preschool age children born preterm and at term. Social risk negatively impacted participation for children born preterm, but not at term. Motor impairment did not appear to influence participation frequency or involvement. Parents of children born preterm perceived more barriers to participation than parents of term‐born children. What this paper adds: Children born preterm attend community activities less often than term‐born children. When attending community activities, involvement was similar between preschool age children born preterm and at term. Social risk negatively impacted participation for children born preterm, but not at term. Motor impairment did not appear to influence participation frequency or involvement. Parents of children born preterm perceived more barriers to participation than parents of term‐born children. This article's abstract has been translated into Spanish and Portuguese. Follow the links from the abstract to view the translations. Video Podcast: https://youtu.be/owVhA4EYVx4 Barreras y facilitadores para la participación comunitaria de niños en edad preescolar nacidos muy prematuros: un estudio de cohorte prospectivo: Objetivo: Comparamos los niños en edad preescolar nacidos muy prematuros con los controles nacidos a término para: (1) comprender la asociación entre el nacimiento muy prematuro y la participación comunitaria, (2) determinar si el deterioro motor o el riesgo social afectan la participación de manera diferente entre los grupos y (3) comprender las barreras ambientales y el apoyo a la participación de los padres. Método: Cuarenta y ocho niños nacidos muy prematuros (<30 semanas de gestación; 22 varones, 26 mujeres) y 96 controles (47 varones, 49 mujeres) fueron evaluados a la edad corregida de 4 a 5 años para la participación comunitaria utilizando la Participación y el Ambiente de Niños Pequeños. Las habilidades motoras se evaluaron utilizando la Batería de evaluación del movimiento para niños, segunda edición y el Cuestionario sobre trastornos de coordinación del desarrollo pequeño. Resultados: Los niños nacidos muy prematuros participaron con menos frecuencia que los niños nacidos a término (diferencia de medias = –0, 28, intervalo de confianza [IC] del 95% –0, 54 a –0, 03, p = 0, 029). El riesgo social se asoció con una menor frecuencia (interacción p <0, 001) y participación (interacción p = 0, 05) en actividades comunitarias para los niños en el grupo muy prematuro solamente. Los padres de niños nacidos muy prematuros percibieron más barreras (razón de posibilidades = 4, 32, IC del 95%: 1, 46‐12, 77, p = 0, 008) y factores ambientales como menos favorables a la participación que los padres de los controles (diferencia en las medianas = –6, 21, IC del 95% –11, 42 a –1, 00, p = 0, 02). Interpretación: Los niños que nacen muy prematuros pueden beneficiarse del apoyo continuo para promover la participación, especialmente en las familias de mayor riesgo social. Barreiras e facilitadores para a participação na comunidade para crianças pré‐escolares nascidas muito prematuras: um estudo de coorte prospectivo: Objetivo: Comparamos crianças em idade pré‐escolar nascidas muito prematuras com crianças nascidas a termo para: 1) entender a associação entre nascimento muito prematuro e participação na comunidade. 2) Determinar se a deficiência motora ou risco social afetam a participação de forma diferente entre gupos, e 3) compreender barreiras e suportes ambientais para a participação de acordo com os pais. Método: Quarenta e oito crianças nascidas muito prematuras (<30 semanas de gestação; 22 do sexo masculino, 26 do sexo feminino) e 96 controles (47 do sexo masculino, 49 do sexo feminino) foram avaliadas nas idade de 4 a 5 anos de idade corrigida quanto à participação na comunidade usando a Medida da participação e do ambiente para crianças pequenas. Habilidades motoras foram avaliadas usando a Bateria de avaliação motora para crianças, segunda edição, e o Questionário de Transtorno do Desenvolvimento da Coordenação de Little. Resultados: Crianças nascidas muito prematuras participaram com menor frequência do que crianças nascidas a termo (diferença na média=–0, 28, intervalo de confiança [IC] a 95%–0, 54 a –0, 03, p =0, 029). O risco social foi associado com menor frequência (interação p <0, 001) e envolvimento (interação p =0, 05) nas atividades da comunidade apenas para crianças no grupo muito prematuro. Os pais de crianças nascidas muito prematuras perceberam mais barreiras (taxa de risco=4, 32, IC 95% 1, 46–12, 77, p =0, 008) e menos apoios quanto aos fatores ambientais para a participação do que os pais dos controles (diferença na média=–6, 21, IC 95% –11, 42 a –1, 00, p =0, 02). Interpretação: Crianças nascidas muito prematuras podem se beneficiar de suporte continuado para promover a participação, especialmente em famílias de maior risco social.